Development of a model of selecting cloud software for a road construction organization under interval information - Kononykhin, Oleksandr (Technology audit and production reserves, 2021)
The object of research is the management processes of a road construction organization. The research is based on the principles of systems analysis for structuring design processes; methods of mathematical modeling, fuzzy mathematics, discrete programming, multicriteria assessment and optimization for the selection of cloud software for road construction organizations in terms of interval information. The information system of a road construction organization includes planning, reporting, regulatory and technical documentation that characterizes the state and movement of information in the enterprise. It is important to use systems that speed up the generation, processing and preparation of documents, as well as improve the storage and retrieval of information. The introduction of cloud technologies has become a necessary condition for increasing the mobility, flexibility and efficiency of the management system of a road construction organization. Formalized processes of information collection and internal distribution can better predict the dynamics of market trends and act more quickly, make decisions confidently and reasonably. In the final stages of selection for assessment, it is convenient to apply the criteria in conditions of interval uncertainty. The study was aimed at improving the efficiency of transport management by developing a model for choosing the cloud software of a road construction organization in terms of interval information. The following criteria of partial optimization were used in the developed model: maximum speed of execution of functions by cloud software; minimum cloud software requirements for internet connection speed; minimum cost of cloud software. The scope of permissible solutions is determined by restrictions: – execution of all functions must be provided by cloud software; – the minimum speed of execution of functions by the cloud software should be not lower than set; – cloud software requirements for Internet connection speed should not exceed the specified; – the cost of cloud software should be no more than specified. The developed model will reduce the cost of purchasing cloud software and increase the efficiency of transport management of a road construction organization.